(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to the psychological characteristics of the influence of self-esteem on the formation of self-confidence in adolescence. Initially, an analysis of theoretical approaches to the manifestation of self-confidence in adolescence is presented. At the same time, the issue of the influence of self-esteem on the formation of self-confidence in adolescence was investigated based on empirical data.